Intrathecal Injections in Children With Spinal Muscular Atrophy: Nusinersen Clinical Trial Experience. (June 2016) - Haché, Manon; Swoboda, Kathryn J.; Sethna, Navil; Farrow-Gillespie, Alan; Khandji, Alexander; Xia, Shuting; Bishop, Kathie M.
Nusinersen (ISIS-SMNRx or ISIS 396443) is an antisense oligonucleotide drug administered intrathecally to treat spinal muscular atrophy. We summarize lumbar puncture experience in children with spinal muscular atrophy during a phase 1 open-label study of nusinersen and its extension. During the studies, 73 lumbar punctures were performed in 28 patients 2 to 14 years of age with type 2/3 spinal muscular atrophy. No complications occurred in 50 (68%) lumbar punctures; in 23 (32%) procedures, adverse events were attributed to lumbar puncture. Most common adverse events were headache (n = 9), back pain (n = 9), and post–lumbar puncture syndrome (n = 8). In a subgroup analysis, adverse events were more frequent in older children, children with type 3 spinal muscular atrophy, and with a 21- or 22-gauge needle compared to a 24-gauge needle or smaller. Lumbar punctures were successfully performed in children with spinal muscular atrophy; lumbar puncture–related adverse event frequency was similar to that previously reported in children.